Physiological and Proteomic Responses to Drought in Leaves of Amygdalus mira (Koehne) Yü et Lu - Xu, Liping; Hu, Yanbo; Jin, Guangze; Lei, Pei; Sang, Liqun; Luo, Qiuxiang; Liu, Zhi; Guan, Fachun; Meng, Fanjuan; Zhao, Xiyang (Frontiers in Plant Science, 2021)
Plant development is strongly influenced by various environmental stresses. Among them, drought is a serious threat which can reduce agricultural productivity and obstruct plant growth. Although the mechanism of plants on responding to drought stress has been studied extensively, the adaptive strategies of Amygdalus Mira (Koehne) Yü et Lu grown in drought and re-watered habitats remain undefined. A. mira from the Tibetan Plateau has outstanding nutritional and medicinal values, and can thrive in extreme drought. In this paper, the physiological and proteomic responses in leaves of A. mira were investigated during the period of drought stress and recovery. The changes of plant growth, photosynthesis, enzymes and non-enzymatic antioxidant under drought and re-watering were also analyzed in leaves. Compared with controls, A. mira showed stronger adaptive and resistant characteristics to drought stress. In addition, proteomic technique was also be used to study mechanisms of drought tolerance in A. mira leaves. Differentialy expressed proteins were identified using mass spectrometry. Accordingly, 103 proteins involved in 10 functional categories: Cytoskeleton dynamics, Energy metabolism, Carbohydrate metabolism, Photosynthesis, Transcription and translation, Transport, Stress and defense, Molecular chaperones, Other materials metabolism, and Unknown function were identified. These results showed that increase of stress-defense-related proteins in leaves after drought treatment were contributed to cope with drought stress. Importantly, A. mira developed adaptive mechanism to scavenge reactive oxygen species (ROS), including enhancement of antioxidant enzymes activities and non-enzymatic low molecular, reduction of energy, and efficiency of adjusting gas exchanges. These results may help to understand the adaptation of A. mira to drought.